Hubungan Konsep Diri dan Kecerdasan Emosional dengan Stres Kerja pada Pendeta Geraja Batak Karo Prostestan di Wilayah Langkat - Elly Enjelita; Nefi Darmayanti; Azhar Aziz (Universitas Medan Area, 2019)
This study was aims to determine the relationship of self concept and emotional intelliegence with work stress of reverence Gereja Batak Karo Protestan (GBKP) in Langkat area. The population of this study are reverences that serve the churches GBKP in Langkat area, consisting of : Klasis Binjai Langkat and Klasis Kuala Langkat as many as 42 people with total sampling tecnique. Data collected by questionnaire. The data collected were analyzed using desciptive tecnique, nalaysis erquirements test, and hypothesis test. Based on the anaysis performed, the result obtained : 1) There is a significant negative relationship between self-concept with work stress, value R2 = 0,112 means self concept given 11,2 % contribution to explain work stress, this means the more negative self concept then the higher the work stress. 2) There is a significant negative relationship between the emotional intelliegence with work stress, R2= 0,278 means emotional intelliegence given 27,8 % contribution to explain work stress, this means lower the emotional intelliegence then the higher the work stress. 3) There is a significant negative relationship between the self concept and emotional intelliegence together with work stress, value R2 = 0,306 means self concept and emotional intelliegence given 30,6% contribution to explain work stress, this means negative self concept and lower the emotional intelliegence then the higher the work stress.